On the possession and attribution problems for collective know-how - Morales Carbonell, Felipe (Aufklärung: journal of philosophy, 2024)
In this paper, I examine two issues that any account of know-how, but particularly an account of group know-how, needs to deal with: the possession problem, which is the need to explain how a group can be in a state of knowing how to do something, and the attribution problem, which is the need to account for the conditions in which it is admissible to attribute know-how to a group. I argue that (despite some initial appearances) they are independent problems, which is specially important in the context of theories where know-how cannot in general be reduced to proposition-oriented attitudes.